Exploring trophy hunting and recreational hunting tourism: an analysis from a bibliometric perspective (1971–2024) - Caro-Barrera, José Rafael; de los Baños García-Moreno García, María; Pérez Priego, Manuel Adolfo (Transformations In Business & Economics, 2026)
Recreational and trophy hunting are controversial practices that intersect ecological conservation, ethical debates and socio-economic development. Only a few studies have been conducted on this subject; thus, this study analyses scientific literature on recreational and trophy hunting by applying the systematic literature network analysis methodology. It uses bibliometric software Bibliometrix and VOSviewer© to analyse a total of 1,559 scientific publications short-listed from the Web of Science© and Scopus© databases from 1971 to 2024. Geographically, there is a lack of research in regions with a hunting tradition. The study contribution extends to the academic and policy areas, establishing a basis for guiding future research and informed policymaking on trophy hunting with socio-economic benefits.
Keywords: Hunting Tourism; Sustainable Tourism; Ethics; Wildlife Conservation; Socio-economic Impact